2018
DOI: 10.1016/j.jaci.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for IL-18 in transformation and maturation of naive eosinophils to pathogenic eosinophils

Abstract: Capsule Summary The current studies demonstrate a critical role of IL-18 in transforming IL-5 generated naïve eosinophils into the distinct inflammatory CD101+CD274+ expressing mature and activated tissue eosinophils that promote disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 11 publications
(19 reference statements)
12
44
1
Order By: Relevance
“…We recently reported that IL‐18 has a critical role in eosinophil differentiation and maturation of pathogenic CD274 + CD101 + ‐expressing eosinophils . This report also indicated that both CD101‐ and CD274‐expressing eosinophils exist in the blood of normal humans and mice, and accumulate in the tissue during allergic conditions in response to IL‐18 . The current study precisely establishes the role of IL‐18 in eosinophil‐associated intestinal disorder.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…We recently reported that IL‐18 has a critical role in eosinophil differentiation and maturation of pathogenic CD274 + CD101 + ‐expressing eosinophils . This report also indicated that both CD101‐ and CD274‐expressing eosinophils exist in the blood of normal humans and mice, and accumulate in the tissue during allergic conditions in response to IL‐18 . The current study precisely establishes the role of IL‐18 in eosinophil‐associated intestinal disorder.…”
Section: Discussionsupporting
confidence: 80%
“…Induction of IL‐18 is reported in allergen‐induced gastrointestinal diseases, including food allergy, but the significance and mechanism of IL‐18 in EGID is not well understood. We recently reported that IL‐18 has a critical role in eosinophil differentiation and maturation of pathogenic CD274 + CD101 + ‐expressing eosinophils . This report also indicated that both CD101‐ and CD274‐expressing eosinophils exist in the blood of normal humans and mice, and accumulate in the tissue during allergic conditions in response to IL‐18 .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations